Two dopamine receptors play different roles in phase change of the migratory locust - Guo, Xiaojiao; Ma, Zongyuan; Kang, Le (Frontiers in Behavioral Neuroscience, 2015)
The migratory locust, Locusta migratoria, shows remarkable phenotypic plasticity at behavioral, physiological, and morphological levels in response to fluctuation in population density. Our previous studies demonstrated that dopamine (DA) and the genes in the dopamine metabolic pathway mediate phase change in Locusta. However, the functions of different dopamine receptors in modulating locust phase change have not been fully explored. In the present study, DA concentration in the brain increased during crowding and decreased during isolation. The expression level of dopamine receptor 1 (Dop1) increased from 1 h to 4 h of crowding, but remained unchanged during isolation. Injection of Dop1 agonist SKF38393 into the brains of solitary locusts promoted gregarization, induced conspecific attraction-response and increased locomotion. RNAi knockdown of Dop1 and injection of antagonist SCH23390 in gregarious locusts induced solitary behavior, promoted the shift to repulsion-response and reduced locomotion. By contrast, the expression level of dopamine receptor 2 (Dop2) gradually increased during isolation, but remained stable during crowding. During the isolation of gregarious locusts, injection of Dop2 antagonist S(–)-sulpiride or RNAi knockdown of Dop2 inhibited solitarization, maintained conspecific attraction-response and increased locomotion; by comparison, the isolated controls displayed conspecific repulsion-response and weaker motility. Activation of Dop2 in solitary locusts through injection of agonist, R(−)-TNPA, did not affect their behavioral state. Thus, DA-Dop1 signaling in the brain of Locusta induced the gregariousness, whereas DA-Dop2 signaling mediated the solitariness. Our study demonstrated that Dop1 and Dop2 modulated locust phase change in two different directions. Further investigation of Locusta Dop1 and Dop2 functions in modulating phase change will improve our understanding of the molecular mechanism underlying phenotypic plasticity in locusts.